Pittori Contemporanei in Olande e Nelle Fiandre - Bekkers, Ludo; Stegeman, Elly (Rekkem : Stichting Ons Erfdeel, 1995)
Vanderheyden, JCJ ; Lucassen ; Verhoef, Toon ; van Koningsbruggen, Rob ; Daniëls, René ; Dumas, Marlene ; Schouten, Marien ; Akkerman, Philip ; Mulders, Marc ; Schuil, Han ; Breedveld, Marian ; Birza, Rob ; Broek, Hans ; Schleiffert, Charlotte ; van Lieshout, Erik ; van Severen, Dan ; de Keyser, Raoul ; Dierickx, Karel ; Bervoets, Fred ; van Bergen, Thé ; Vandenberg, Philippe ; Fabre, Jan ; Tuymans, Luc ; (van Innis), Benoît ; Dillemans, Sam
boek